The Role of Work Fatigue and Employee Engagement As Mediators in The Relationship Between Work Stress And Workload on Employee Turnover Rates at Waste Paper Raw Material Supplier Companies in Serang Regency - Fikri, Muhammad; Basrowi, Basrowi; Khaeruman, Khaeruman (CV. Publikasi Indonesia, 2025)
This study aims to determine the role of job fatigue (KK) and employee engagement (K) in mediating the relationship between job stress (SK) and workload (BK) on employee turnover (TK) in a waste paper raw material supplier company. By using the quantitative correlational method, the sample used was 205 respondents, and using the statistical analysis method with smartPLS 3 software. The results found in this study refer to the hypothesis of direct and indirect influence, which there are 12 hypotheses. With the results showing SK has a positive effect on TK with a p-value of 0.032 ≤ 0.05 . BK has a positive effect on TK with a p-value of 0.000 ≤ 0.05 . KK has a positive effect on TK with a p-value of 0.002 ≤ 0.05 , K has no effect on TK with a p-value of 0.099 ≥ 0.05. SK has a positive effect on KK with a p-value of 0.000 ≤ 0.05 , BK has a positive effect on TK with a p-value of 0.008 ≤ 0.05. SK and BK have no effect on K with a p-value of 0.212 & 0.630 ≥ 0.05 . Indirectly SK and BK have a positive effect on TK through KK p-value of 0.008 & 0.024 ≤ 0.05 . And K has no mediating role. In this study, it can be concluded that work stress, workload, and work fatigue have a positive effect on turnover, while engagement has no effect. And work fatigue plays a mediating role in the relationship between increased work stress and workload on employee turnover, and engagement does not find a mediating role.